Android-based learning media on human respiratory system material for high school students - Mirra Fatharani; Dwi Maihidin Pahlifi (Jurnal Inovasi Pendidikan IPA, 2019)
This research was aimed to produce a product in the form of android-based learning media on the material of the human respiratory system for the Science Class students in XI Grade of High School. This research was performed in SMA Negeri 2 Bantul. The biology learning through the utilization of this android-based learning media has a characteristic which utilizes technology in learning, therefore, it could be used by anyone, anywhere, and anytime. The method used in this development research was based on the adaptation of ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The initial product has been reviewed by the material and media experts. Then, the result of revision was assessed based on materials, operationalization, and the media display conducted by reviewers (biology teacher) and peer reviewers. Then, it tested on high school students to discover the feasibility of android-based learning media. The research results have indicated that android-based learning media on the material of human respiratory system which has been developed was assessed as feasible to be implemented in the learning reviewed from the aspect of material assessment which included in the criteria of “very good”, the aspect of media assessment showed “very good” criteria as well and the test result toward the students included in “very good” category.